Heightened Vulnerability of Alzheimer's disease in COVID-19 Cataclysm and Putative Management Strategies - Mohammad Azizur Rahman; Mohammad Saidur Rahman; Nur Alam (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2020)
Alzheimer's Disease (AD) susceptibility has been soared during global pandemic of coronavirus disease 2019 (COVID-19). People of advanced ages, especially those over sixty years old are more vulnerable to AD and COVID-19 conundrum. Concordant and discordant etiology, pathophysiology and management strategies of AD and COVID-19 had been highlighted in this review. Considering the grave concern of AD and COVID-19 specifically on global aged old population, some recommendations for managing both of the crises had been put forward.